2017
DOI: 10.1002/ecy.1911
|View full text |Cite
|
Sign up to set email alerts
|

Local density regulates migratory songbird reproductive success through effects on double‐brooding and nest predation

Abstract: Knowledge of the density-dependent processes that regulate animal populations is key to understanding, predicting, and conserving populations. In migratory birds, density-dependence is most often studied during the breeding season, yet we still lack a robust understanding of the reproductive traits through which density influences individual reproductive success. We used 27-yr of detailed, individual-level productivity data from an island-breeding population of Savannah sparrows Passerculus sandwichensis to ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 60 publications
1
18
0
Order By: Relevance
“…Our results show that fledging success is also strongly negatively associated with high productivity in the previous year. Although we did not have the capacity to run a corresponding control study in order clearly to demonstrate a causal link between changes in nestbox availability and breeding metrics, the correlation from our study is strongly supported by other studies (Both 1998, Newton 1998, Dhondt 2010, Nicolaus et al 2012, Woodworth et al 2017, Møller et al 2018). Lower densities of breeding Great Tits have been shown by both observational and experimental studies to have higher reproductive output via mechanisms including increased clutch size, fledgling mass and double‐brooding (Kluijver 1951, Both 1998, 2010, Dhondt 2010).…”
Section: Discussionsupporting
confidence: 80%
“…Our results show that fledging success is also strongly negatively associated with high productivity in the previous year. Although we did not have the capacity to run a corresponding control study in order clearly to demonstrate a causal link between changes in nestbox availability and breeding metrics, the correlation from our study is strongly supported by other studies (Both 1998, Newton 1998, Dhondt 2010, Nicolaus et al 2012, Woodworth et al 2017, Møller et al 2018). Lower densities of breeding Great Tits have been shown by both observational and experimental studies to have higher reproductive output via mechanisms including increased clutch size, fledgling mass and double‐brooding (Kluijver 1951, Both 1998, 2010, Dhondt 2010).…”
Section: Discussionsupporting
confidence: 80%
“…Neither clutch size nor fledging success were affected by the weather variables we considered, supporting the idea of environmental canalization (Gaillard & Yoccoz, ). Fledging success could have been affected by variables we did not test or nonweather variables, such as changes in predator population densities or activity (Cox, Thompson, & Faaborg, ; Cox, Thompson, & Reidy, ), improved search image and long‐term memory of predators (Bailey & Bonter, ), variations in parental feeding behavior (Martin, Scott, & Menge, ) or female brooding (DuRant, ; DuRant, Hepp, Moore, Hopkins, & Hopkins, ), or density of bluebirds and competitor species (Alatalo & Lundberg, ; Woodworth, Wheelwright, Newman, & Norris, ). Additionally, fledging success could have been affected by weather variables in a nonlinear fashion (Chen, Wang, Wan, & Liu, ; Stenseth & Mysterud, ), which we did not test.…”
Section: Discussionmentioning
confidence: 99%
“…The Kent Island Savannah sparrows were first recorded in the early 1980s by Clara Dixon; a few recordings from 1988 and 1989 also exist, and extensive song recordings are available for the years from 1993 to 1998 and 2003 to 2019 (see . Because Nathaniel Wheelwright began a longterm population study that mapped territories and color-banded breeding adults as well as nestlings in 1987 in this philopatric population (Wheelwright and Mauck, 1998), an enterprise that was continued by Ryan Norris and his colleagues (Woodworth et al, 2017), we have extensive demographic data to go with the song recordings of identified males. Each male sings one song that does not change after crystallization early in the first breeding season .…”
Section: Long-term Studiesmentioning
confidence: 99%